Essays in corporate finance - LI, Bingqiao (Institutional Knowledge at Singapore Management University, 2016)
Based on a constructed index measuring the corporate governance quality of public firms, this paper focus on the role of corporate governance and its association with the performance of Singapore Exchange listed firms. We investigate the following three aspects centred on the topic of firm corporate governance in Singapore. First, we examine the performance of the Chinese firms listed on the Singapore Exchange (S-Chips) and the role of their corporate governance. S-Chips indeed underperform local firms in terms of Tobin’s Q within both univariate and multivariable frameworks, as well as base on size matched and Propensity Score Matching samples. Higher index value indicating good governance is found to be positively related to higher Tobin’s Q for the full sample; however, when firms are separated into difference groups based on firm’s location characteristics, we find that the above positive relationship vanishes and even reverse sign when applying to firms falling into the S-Chip group. Such negative result is future supported by robustness tests that take size, firm holdings pattern and other firm characteristics into account. The results thus support our view that S-Chips are suffering from low valuation due to their “notorious reputations” caused by the scandalous actions of the managements of some former companies involved with scandals and that governance quality revealed by the S-Chips’ managements through public resources are not regarded as trust worthy by the market. Second, we investigate the relationship between firm’s government ownership, particularly the fractions of common stocks held by Temasek Holdings, and firm value within the corporate governance framework based on a sample of Singapore Exchange listed firms. We make comparison between firm valuation and corporate governance index (SCGI) of firms that have Temasek investments (TLCs) and firms that do not (non-TLCs) and found that TLCs tend to have both higher corporate governance score and Q value and the results are consistent based on the analyses of both multivariable regression and simultaneous regressions. Temasek stock holdings are found to be related to higher firm Tobin’s Q value beyond the level of Q that is associated with good corporate governance for the full sample. Better corporate governance of TLCs are robust to matched samples based on firm size and PSM score; however, results for firm value based on matched samples indicates that it is the differences in firm characteristics such as size, leverage and profitability that drive the different firm values between TLCs and their non-TLC counterparties. No statistical significance differences are found for the positive relationship of firm value and corporate governance between TLCs and non-TLCs Third, we look at the impact of firm’s corporate governance practice on reducing agency costs. We choose two proxies to quantify agency costs, namely asset turnover as an inverse measure, and free cash flow as a direct measure. Controlling for growth prospects, we find a positive linear relationship between firm asset utilization (asset turnover) and governance quality, consistent with the notion that effective corporate governance can help mitigate agency problems. Furthermore, we find a nonlinear inverted U-shaped relationship between agency costs and corporate governance when using the interaction of free cash flow and firm growth opportunities as the direct agency costs proxy. Free cash flows are not kept with firms that have the best corporate governance performance when no positive NPV investment opportunities are available. Sub-indices analysis reconfirms the importance of roles of stakeholders and the responsibilities of the board of directors.